Optimization Extraction of Anthocyanin from Roselle as a Natural Colorant using Natural Deep Eutectic Solvent with Microwave Assisted Extraction Method - Ade Kurnianto; Aji Prasetyaningrum; Vita Paramita (Vocational College of Universitas Diponegoro, 2025)
Roselle (Hibiscus sabdariffa L.) contains high levels of anthocyanins with significant antioxidant properties. However, conventional extraction methods often result in low efficiency and degradation of bioactive compounds. This study aims to optimize the extraction of anthocyanins from roselle using Microwave Assisted Extraction (MAE) with Natural Deep Eutectic Solvent (NADES) combination of sodium acetate and glycerin then examine the effect of optimum anthocyanin content. The variables applied were microwave power (200, 400, 600 Watt) and extraction time (4, 6, 8 min), optimized using Response Surface Methodology (RSM) with 12 experimental runs. Analysis included antioxidant content (anthocyanins, vitamin C, tannins, and total phenolics) and stability tests (density and viscosity). The RSM results have shown that the optimization value of anthocyanin content is 0.3217%, which will be achieved at an extraction time of 6.02 min, and microwave assisted extraction power at 323.77 Watt. The result of the optimum anthocyanin variable shows anthocyanin content is 0.3072% confirming the model's accuracy. MAE combined with NADES provides an efficient and environmentally friendly method for extracting natural colorants with high antioxidant activity from roselle.